2017
DOI: 10.1016/j.canlet.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

PAD1 promotes epithelial-mesenchymal transition and metastasis in triple-negative breast cancer cells by regulating MEK1-ERK1/2-MMP2 signaling

Abstract: Peptidylargininedeiminase 1 (PAD1) catalyzes protein for citrullination, and this activity has been linked to the epidermal cornification. However, a role for PAD1 in tumorigenesis, including breast cancers has not been previously explored. Here we first showed that PAD1 is overexpressed in human triple negative breast cancer (TNBC). In cultured cells and xenograft mouse models, PAD1 depletion or inhibition reduced cell proliferation, suppressed epithelial-mesenchymal transition, and prevented metastasis of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 54 publications
7
62
0
Order By: Relevance
“…Consistent with data described above, in human triple-negative breast cancer (TNBC), PAD1 was shown to induce EMT through suppressing ERK1/2 and P38 MAPK signaling through direct citrullination of MEK1 (60). This resulted in disrupting MEK1mediated phosphorylation of ERK1/2, eventually leading to MMP2 overexpression, eventually triggering EMT.…”
Section: Citrullination and Epithelial-to-mesenchymal Transitionsupporting
confidence: 72%
“…Consistent with data described above, in human triple-negative breast cancer (TNBC), PAD1 was shown to induce EMT through suppressing ERK1/2 and P38 MAPK signaling through direct citrullination of MEK1 (60). This resulted in disrupting MEK1mediated phosphorylation of ERK1/2, eventually leading to MMP2 overexpression, eventually triggering EMT.…”
Section: Citrullination and Epithelial-to-mesenchymal Transitionsupporting
confidence: 72%
“…ERK1/ c-MYC axis was identified as a major pivot in PRKD3-regulated pathways in tumour cells. [24][25][26] In mammals, the identity of ERK1 and ERK2 sequences is 84%, but ERK1 has two more amino acids (a.a.) at its C-terminus and 17 more a.a. at N-terminus than ERK2. 13 The extracellular signal-regulated kinase 1/2 (ERK1/2) can be activated and/ or up-regulated by upstream kinases, transcription factors and/ or differentiation factor.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] These ERK1/2-activated downstream factors further regulate many cellular functions, including proliferation, differentiation and transformation. [24][25][26] In mammals, the identity of ERK1 and ERK2 sequences is 84%, but ERK1 has two more amino acids (a.a.) at its C-terminus and 17 more a.a. at N-terminus than ERK2. 27 Most previous studies had indicated that the functions of ERK1 and ERK2 were redundant, and they usually worked together as a fundamental unit to regulate cellular functions in organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, inhibition of PAD2 in breast cancer cell lines decreases disease progression by increasing apoptosis (McElwee et al 2012). Recently, PAD1 was shown to be overexpressed in human triple-negative breast cancer lines (e.g., MDA-MB-231 cells) as well as in xenograft mouse models and its inhibition resulted in reduced cell proliferation and metastasis (Qin et al 2017). PAD2 and PAD4 are also activated in the central nervous system (CNS) during neurodegenerative processes and are observed to be co-localized in regions of degraded neurons in Alzheimer’s patients (Acharya et al 2012; Ishigami et al 2005).…”
Section: Introductionmentioning
confidence: 99%